Pengembangan Sistem Point of Sales berbasis Web (Studi Kasus: Sedudam Cafe) - Hafiz Maulana; Denny Sagita Rusdianto; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The café nowadays not only provides food, but also plays an important role in the political, cultural and social aspects of daily life for tourists and the citizens itself. The number of cafes in Malang which recorded by BP2D is 144 cafes, one of them is Sedudam Cafe which is located in the Soekarno-Hatta area. Sedudam Café uses a cashier application called SPOTS to assist sales transactions which can only carry out cashier transactions in general, such as menu selling and receipt printing transactions. SPOTS has problems in terms of financial calculation, such as calculating profit and tracking raw material stock problems. Based on these problems, there is a solution that can be used, which is the web-based Point of Sales (POS) system. In the POS System, there are features found in the system, which are the features of sales, inventory, raw material stock tracking and reporting modules. In this study, the waterfall method is used for system development. There are 48 functional requirements and 1 non-functional requirement in this development. Functional testing used in this development is validation testing and unit testing which produces 100% valid. Non-functional testing uses compatibility testing which results in the system running multiple browsers, they are Firefox and Chrome. This development is expected to be able to help solve the problems in Sedudam Café.